Empirical reconstruction and long-duration tracking of the magnetospheric boundary in single- and multi-spacecraft contexts - J. De Keyser (Annales Geophysicae, 2005)
The magnetospheric boundary is always moving, making it difficult to establish its structure. This paper presents a novel method for tracking the motion of the boundary, based on in-situ observations of the plasma velocity and of one or more additional observables. This method allows the moving boundary to be followed for extended periods of time (up to several hours) and aptly deals with limitations on the time resolution of the data, with measurement errors, and with occasional data gaps; it can exploit data from any number of spacecraft and any type of instrument. At the same time the method is an empirical reconstruction technique that determines the one-dimensional spatial structure of the boundary. The method is illustrated with single- and multi-spacecraft applications using data from Ampte/Irm and Cluster.